EFL Teachers' Attitudes toward E-learning Platforms during the Covid-19 Pandemic - Syahputra, Bambang Panca; Saragih, Erikson (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2021)
This study investigates the features of three e-learning platforms: Moodle, Google Classroom, and Zoom. It provides an in-depth examination of the digital learning media efficacy during the COVID-19 pandemic. It outlines the advantages and disadvantages of e-learning platforms for English language teaching. The research highlights the potential of authentic e-learning platforms to motivate EFL teachers and students to step up to the challenge. A digital survey which consisted of 36 items, was distributed to determine EFL teachers' impressions of the effectiveness of these platforms. The researchers distributed three questionnaires for each e-learning platform. Each questionnaire consisted of six sections: availability and accessibility, efficiency, information exchange, teacher perception, teacher satisfaction, and E-learning insight during COVID-19. The researchers utilized the Minitab 16 Statistical software to analyze the elicited data and the Cronbach's Alpha values to assess the survey questions content validity. Other statistical techniques, such as mean, standard deviation, and agreeable level (AR), were used to depict the effectiveness of each platform. Google Classroom (Ave. AR = 72.92 percent and Ave. Mean = 3.887) was the most efficient e-learning platform based on the survey responses.  The next platforms were Moodle (Ave. AR = 68.09 percent, Ave. Mean = 3.694) and Zoom (Ave. AR = 61.85 percent, Ave. Mean = 3.544). The findings should motivate language learners to act and assist instructors and policy-makers in constructing e-learning environments that support learning during the global health crisis.